Influencing factors in tourist decision-making: Lifestyle, art collections, and hedonic motivations at the National Gallery - Mukarommah, Amirah Salwa; Tuti, Meylani (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2023)
Tourism-related activities play a crucial role in the global economy, driven by diverse factors influencing tourists’ destination choices. This study focuses on understanding the factors that influence tourists' decisions to visit the National Gallery, emphasizing lifestyle, art collections, and hedonic motivations. Utilizing a quantitative research method, data was collected from 152 visitors through a structured questionnaire and analyzed using Structural Equation Modeling (SEM) with smart PLS software. The findings reveal that hedonic motivations significantly impact visit intentions, decisions, and revisit intentions, highlighting the role of pleasure and enjoyment in attracting visitors. Art collections also influence visit and revisit intentions but do not significantly affect the initial visit decision. Conversely, lifestyle factors showed no significant impact on visiting decisions. These results provide valuable insights for tourism marketers and planners to enhance visitor engagement and satisfaction by focusing on hedonic and art-related motivations. The study contributes to the existing literature by integrating these variables and offers actionable strategies for the National Gallery and similar institutions.